2012
DOI: 10.1007/s13181-012-0213-7
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Weight Loss Agents

Abstract: Introduction: With the rise of the obesity epidemic in the United States over the last several decades and the medical complications seen with it, weight loss and dieting have become a national public health concern. Discussion: Because of their increased use and availability through internet sales, several different dieting agents were reviewed for potential toxicity. These included: syrup of ipecac, cathartics, human chorionic gonadotropin hormone, 2,4 Dinitrophenol, guar gum, phenylpropanolamine, ma huang/ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
67
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(69 citation statements)
references
References 62 publications
(72 reference statements)
1
67
0
1
Order By: Relevance
“…From the public health point of view, it is concerning that hazards of the past seem to be a permanent or returning feature of today's off-street 'supplement' market, mainly through retail networks that fall outside standard safety regulations: the Internet 1 . 2,4-Dinitrophenol (DNP) was used until the late 1930s to treat obesity and was subsequently withdrawn owing to its severe toxicity 2 . However, industrial uses of DNP as a dye, wood preserver, herbicide and film-developer have remained in place over the years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the public health point of view, it is concerning that hazards of the past seem to be a permanent or returning feature of today's off-street 'supplement' market, mainly through retail networks that fall outside standard safety regulations: the Internet 1 . 2,4-Dinitrophenol (DNP) was used until the late 1930s to treat obesity and was subsequently withdrawn owing to its severe toxicity 2 . However, industrial uses of DNP as a dye, wood preserver, herbicide and film-developer have remained in place over the years.…”
Section: Introductionmentioning
confidence: 99%
“…However, the weight-loss effect comes with serious, and in some cases potentially fatal, adverse side effects. These include hyperthermia (the leading cause of fatality with acute DNP toxicity) and cardiac arrest, but also diaphoresis, tachycardia, tachypnea; and cataracts with low dose chronic exposure [2][3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…Simeons noticed that these men lost their ravenous appetite and noticed redistribution of their body fat. [2][3][4] In pregnancy, Simeons suggested that HCG prevents the formation of abnormal fat deposits in order to maintain maternal blood saturated with nutrients to provide adequate caloric requirement for fetal growth. 4,5 The diet consists of the intramuscular injection of 125 IUs of B-HCG 6 times per week for a total of 40 injections.…”
Section: Discussionmentioning
confidence: 99%
“…2, 4-Dinitrophenol (DNP) has historically been used in the manufacture of food coloring, clothing dyes, explosives, agricultural herbicides, insecticides and fungicides [1,2]. The compound is known to uncouple mitochondrial oxidative phosphorylation and was used as an antiobesity agent early in the past century.…”
Section: Introductionmentioning
confidence: 99%